AN ERROR ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS' DESCRIPTIVE TEXTS - Rohmah, Ida Faiqotur (2017)
In second language acquisition, errors are commonly made by the second language students in the process of learning the second language. The current study is aimed to investigate the most dominant error type in the students' descriptive texts based on the general classification of errors presented by Corder (1981) and Ellis (1997). It is also aimed to find out the sources of errors based on the students' point of view. The qualitative case study was employed as the research design in this study. Thirty one of eighth grade students were involved as the research participants. The data were collected through documenting students' descriptive texts in two writing tasks, and interviews. The results of the study showed that the most dominant error type in the students' descriptive texts was omission. The next errors were misselection, addition, and misordering. In this study, the students perceived that the sources of their errors were difficulty in translating the texts, the lack of English vocabularies and their meanings, having not understood the English grammar, and the assumption that writing in English is difficult. Therefore, it is better for the teacher to give exposure on the explanation of sentence structures. By doing so, hopefully the error of omission can be avoided by the students. ;--- Dalam pemerolehan Bahasa kedua, eror biasanya dilakukan oleh pembelajar Bahasa kedua dalam proses mempelajari Bahasa kedua tersebut. Penelitian ini bertujuan untuk meneliti tipe error yang paling dominan pada teks deskriptif siswa berdasarkan klasifikasi umum eror menurut Corder (1981) dan Ellis (1997). Penelitian ini juga bermaksud meneliti sumber eror tersebut menurut pandangan para siswa. Dalam penelitian ini, studi kasus kualitatif digunakan sebagai desain penelitian.Tiga puluh satu siswa dilibatkan sebagai partisipan penelitian. Data dalam penelitian ini dikumpulkan melalui pengumpulan teks deskriptif siswa dalam dua tugas menulis, dan wawancara. Hasil penelitian ini menunjukkan bahwa tipe error paling dominan pada teks deskriptif siswa adalah omission. Selanjutnya diikuti oleh misselection, addition, dan misordering. Dalam penelitian ini, siswa memiliki persepsi bahwa sumber eror mereka adalah kesulitan dalam menerjemahkan teks, kurangnya perbendaharaan kata bahasa Inggris dan maknanya, belum memahami tata Bahasa Inggris, dan asumsi bahwa menulis dalam Bahasa Inggris itu sulit. Oleh sebab itu, sebaiknya guru memberikan penekanan dalam menjelaskan struktur kalimat. Dengan demikian, diharapkan eror omission dapat dihindari oleh para siswa.